Mengintegrasi Bacaan Al-Qur’an Dalam Rutinitas Harian Santri Studi Kasus Majelis Bimbingan Al-Qu’ran Darussalam - Abdul Latif Anshory; Ali Manshur (Jurnal Multidisiplin Indonesia, 2024)
Integrating the reading of the Qur'an into the daily routine of students is one of the efforts made in Islamic boarding schools to shape the religious personality of students. This activity illustrates the existence of a social structure that is formed among the community of students who are accustomed to certain patterns in carrying out their daily lives. This activity reflects the role of Islamic boarding schools as educational institutions that not only focus on teaching religious knowledge, but also on forming a strong religious character. In addition, this activity is also one way to improve the ability of students to read the Qur'an properly and correctly, in accordance with tajwid and makharijul huruf. Not only that, the integration of the reading of the Qur'an also strengthens the relationship between students and teachers and leaders of the Islamic boarding school. The Darussalam Islamic Boarding School served as the study's object of study, and a qualitative research methodology was adopted. In this study, data collection will be carried out through several techniques, including in-depth interviews, participatory observation, and document analysis. Through this interview, researchers can explore information about the motivations, challenges, and benefits they feel from the activity. From the results of the study conducted at the Darussalam Islamic Boarding School, it can be concluded that the integration of Al-Qur'an reading into the daily routine of students has a significant positive impact on the development of their character and spirituality. This is in line with the views of teachers who state that this activity contributes to forming good attitudes among students. Although there are challenges, such as difficulty in understanding the meaning of the verses, support from caregivers and creative teaching methods can help students to be more connected to their reading.